Expression of UV-Sensitive Parapinopsin in the Iguana Parietal Eyes and Its Implication in UV-Sensitivity in Vertebrate Pineal-Related Organs - Wada, Seiji (Public Library of Science, 2012)
The pineal-related organs of lower vertebrates have the ability to discriminate different wavelengths of light. This wavelength discrimination is achieved through antagonistic light responses to UV or blue and visible light. Previously, we demonstrated that parapinopsin underlies the UV reception in the lamprey pineal organ and identified parapinopsin genes in teleosts and frogs of which the pineal-related organs were reported to discriminate light. In this study, we report the first identification of parapinopsin in the reptile lineage and show its expression in the parietal eye of the green iguana. Spectroscopic analysis revealed that iguana parapinopsin is a UV-sensitive pigment, similar to lamprey parapinopsin. Interestingly, immunohistochemical analyses using antibodies specific to parapinopsin and parietopsin, a parietal eye green-sensitive pigment, revealed that parapinopsin and parietopsin are colocalized in the outer segments of the parietal eye photoreceptor cells in iguanas. These results strongly suggest that parapinopsin underlies the wavelength discrimination involving UV reception in the iguana parietal eye. The current findings support the idea that parapinopsin is a common photopigment underlying the UV-sensitivity in wavelength discrimination of the pineal-related organs found from lampreys to reptiles.